Development of Renderforest Technology-Based Mathematics Learning Videos - Wulandari, Wahyu; Hile, Abdulhaviz (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to develop a mathematics learning video based on Renderforest technology. The research method used is creating learning videos based on Renderforest technology for seventh-grade junior high school students. The material chosen is comparison. The research process is design, development, and implementation. The instrument used is a questionnaire with the ARCS model. Assessments in the instrument include attention, relevance, confidence, and satisfaction. Data collection techniques were with student responses. The results of this study are the use of learning videos, students feel the benefits, are easy to use, help in learning mathematics, and provide satisfaction.